2022
DOI: 10.12659/msm.936713
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bromelain-Based Enzymatic Debridement Combined with Laser Doppler Imaging and Healing of Burn Wounds

Abstract: Background Accurate estimation of burn depth is crucial for correct treatment decision making. Bromelain-based enzymatic debridement (ED) may improve clinical assessment of burn depth. Laser Doppler imaging (LDI) provides a valuable indicator of burn depth by analyzing microcirculation within tissue beds. This study aimed to evaluate bromelain-based enzymatic debridement combined with laser Doppler imaging and healing of 42 wounds in 19 patients with mixed second- and third-degree thermal burns. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Bromelain is a viable alternative to surgical escharotomy for deep burns [ 47 ]. In fact, prompt removal of necrotic tissue leads to better spontaneous healing or better graft application, reducing the risk of infection and improving patient survival [ 71 ]. Infection is the leading cause of death in burn patients, especially in children, due to the compromised skin barrier.…”
Section: Use Of Bromelain In Children and Adolescentsmentioning
confidence: 99%
See 3 more Smart Citations
“…Bromelain is a viable alternative to surgical escharotomy for deep burns [ 47 ]. In fact, prompt removal of necrotic tissue leads to better spontaneous healing or better graft application, reducing the risk of infection and improving patient survival [ 71 ]. Infection is the leading cause of death in burn patients, especially in children, due to the compromised skin barrier.…”
Section: Use Of Bromelain In Children and Adolescentsmentioning
confidence: 99%
“…Infection is the leading cause of death in burn patients, especially in children, due to the compromised skin barrier. In addition, the risk of infection persists until necrotic tissue remains [ 71 ]. Therefore, early eschar debridement within 24 h of the burn significantly reduces the risk of bacterial colonization and infection, especially in pediatric patients.…”
Section: Use Of Bromelain In Children and Adolescentsmentioning
confidence: 99%
See 2 more Smart Citations
“…57,66,67 Schulz et al in a study with 40 patients with hand burns found superior outcomes post-BBD in burn depth evaluation, tissue preservation, completeness of debridement, and wound closure. 68 Although Laser Doppler Imaging (LDI), 69,70 and ultrasound for assessing skin thickness 71 may be helpful, subjective clinical inspection of the remaining dermal elements is the standard method for assessing the post-enzymatically debrided wound bed.…”
Section: Safety Profilementioning
confidence: 99%